Argumentation in artificial intelligence - Rahwan, Iyad (Springer, 2009)
Summary: This volume is a systematic, expansive presentation of the major achievements in the intersection between two fields of inquiry: Argumentation Theory and Artificial Intelligence. Contributions from international researchers who have helped shape this dynamic area offer a progressive development of intuitions, ideas and techniques, from philosophical backgrounds, to abstract argument systems, to computing arguments, to the appearance of applications producing innovative results. Each chapter features extensive examples to ensure...
Keywords: Argumentationstheorie; Künstliche Intelligenz; Argumentation